2021
DOI: 10.2217/rme-2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Negative Pressure Wound Therapy Combined with Platelet-Rich Fibrin for Bone-Exposed Wounds

Abstract: Aim: To evaluate the efficacy of negative pressure wound therapy (NPWT) combined with platelet-rich fibrin (PRF) in treating bone-exposed wounds and explore its possible mechanism. Materials & methods: A bone-exposed wound was created in a total of 32 healthy Sprague-Dawley rats, which were treated with either control, NPWT group, PRF group or both (N + P group). The bone-exposed area, skin contraction rate and granulation coverage and the level of growth factors in granulation tissue were determined on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…One study revealed that the osteogenic potential of MSCs can be modulated by mechanical stimulation. Mechanical cues and appropriate stiffness can promote in vitro and endochondral osseointegration and differentiation of MSCs 156 . Several in vitro and in vivo studies have demonstrated that bone regeneration can be accelerated by enhancing MSC proliferation, osteoblast differentiation, and osteogenesis-related cytokine expression through continuous or intermittent NPWT.…”
Section: Biophysical Stimulation For Osteoporotic Osseointegration An...mentioning
confidence: 99%
“…One study revealed that the osteogenic potential of MSCs can be modulated by mechanical stimulation. Mechanical cues and appropriate stiffness can promote in vitro and endochondral osseointegration and differentiation of MSCs 156 . Several in vitro and in vivo studies have demonstrated that bone regeneration can be accelerated by enhancing MSC proliferation, osteoblast differentiation, and osteogenesis-related cytokine expression through continuous or intermittent NPWT.…”
Section: Biophysical Stimulation For Osteoporotic Osseointegration An...mentioning
confidence: 99%